A Study to Assess the Level of Stress, Anxiety and Depression Among Patients with Chronic Kidney Disease in Selected Hospitals, Hosur - Archana V, Archana V; Rajalakshmi, Rajalakshmi (Journal of Neonatal Surgery, 2025)
Background: Chronic kidney disease (CKD) is a major public health concern worldwide, affecting millions of individuals and posing significant challenges to healthcare systems. Methodology: The present study adopted a cross-sectional descriptive study. The sample size is estimated as 60 by using power analysis. The study will include patients aged 18 and above, who given informed consent and diagnosed with chronic kidney disease (CKD) currently receiving dialysis at the Gunam super specialty hospital, Hosur. Patients with severe cognitive impairment or unrelated mental health disorders and those in the acute stages of kidney failure will be excluded from the study. Results: The results show that 30.0% of patients experienced mild depression, 25.0% moderate depression, and 25.0% had no depression. For anxiety, 33.3% had mild anxiety, 30.0% moderate anxiety, and 20.0% had no anxiety. Severe depression, anxiety, and stress were less common, with 20.0%, 16.7%, and 20.0% reporting these conditions, respectively. There are strong positive correlations between depression, anxiety, and stress (r-values 0.72-0.83), with p-values less than 0.001, indicating statistically significant relationships. Conclusion: The study concluded that the there is a significant lack of BLS knowledge among laypersons, with most participants showing inadequate understanding and 80% unaware of BLS. The study highlights the sustained efforts are needed to improve BLS education and training, targeting both healthcare professionals and the general public, to enhance the community's ability to respond to cardiac emergencies and improve survival rates